Biosynthesized silver nanoparticles using Polygonatum geminiflorum efficiently control fusarium wilt disease of tomato - Ahmad, Maaz; Ali, Ahmad; Ullah, Zahid; Sher, Hassan; Dai, Dong-Qin; Ali, Mohammad; Iqbal, Javed; Zahoor, Muhammad; Ali, Iftikhar (Frontiers in Bioengineering and Biotechnology, 2022)
Nanomaterials are gaining tremendous potential as emerging antimicrobials in the quest to find resistance-free alternatives of chemical pesticides. In this study, stable silver nanoparticles were synthesized using the aqueous extract of medicinal plant species Polygonatum geminiflorum, and their morphological features were evaluated by transmission electron microscopy, X-ray diffraction spectroscopy and energy dispersive X-ray analysis. In vitro Antifungal activity of the synthesized silver nanoparticles (AgNPs) and P. geminiflorum extract (PE) either alone or in combination (PE-AgNPs) against Fusarium oxysporum was evaluated using disc-diffusion and well-diffusion methods. In planta assay of the same treatments against Fusarium wilt diseases of tomato was evaluated by foliar spray method. Moreover, plant extract was evaluated for the quantitative investigation of antioxidant activity, phenolics and flavonoids by spectroscopic and HPLC techniques. Phytochemical analysis indicated the presence of total phenolic and flavonoid contents as 48.32 + 1.54 mg GAE/g and 57.08 + 1.36 mg QE/g, respectively. The DPPH radical scavenging of leaf extract was found to be 88.23 + 0.87%. Besides, the HPLC phenolic profile showed the presence of 15 bioactive phenolic compounds. Characterization of nanoparticles revealed the size ranging from 8 to 34 nm with average crystallite size of 27 nm. The FTIR analysis revealed important functional groups that were responsible for the reduction and stabilization of AgNPs. In the in vitro assays, 100 µg/mL of AgNPs and AgNPs-PE strongly inhibited Fusarium oxysporum. The same treatments tested against Fusarium sprayed on tomato plants in controlled environment exhibited nearly 100% plant survival with no observable phytotoxicity. These finding provide a simple baseline to control Fusarium wilt using silver nano bio-control agents without affecting the crop health.